The Effect of Educational, Health, Infrastructure Expenses on the Workforce Employment and Poverty - Sulistyowati, Niken (UI Scholars Hub, 2014)
The research aims to analyze the influence and impact of educational, health, and infrastructure expenses on the employment of workforce (from agricultural, industrial, services sectors) and poverty in Central Java. The model was built by using an econometric approach in the form of a system of simultaneous equation model consisting of six blocks (human capital, inputs, outputs, revenues, expenditures and social welfare) with 33 equations (24 structural equations and 9 identity equation). The method of estimation model uses Two Stage Least Squares (2SLS). The simulation results show that the policies of increasing expenses on education, health, and infrastructure with the same value result in the increased employment of workforce in all sectors and reduced poverty. Among these policies, the increased health expenses have the most significant influence on the increase of workforce employment in services sector and reduce poverty. While the policy of increasing expenses on infrastructure has the greatest effect on the increase of workforce employment in industrial and agricultural sectors.